Pelatihan Penggunaan Teknologi untuk Pengajaran Bahasa Inggris secara Inovatif Di Kelas untuk Guru-Guru MGMP Bahasa Inggris di Kabupaten Bantul - Daniel Ari Widhiatama; Dangin Dangin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The application of CALL (Computer Assisted Language Learning) and MALL (Mobile Assisted Language Learning) based technology in language learning in the classroom is not new in this era. A variety of applications are available for free on the internet. However, the knowledge of teachers in Indonesia about the functions and ways of implementing these applications is still low. With this training, it is hoped that teachers will be increasingly able to use CALL and MALL-based applications and explain the pedagogical side simultaneously.